2016
DOI: 10.1111/jcmm.12997
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let‐7g possesses a therapeutic potential for peripheral artery disease

Abstract: Peripheral artery disease (PAD) is a manifestation of systemic atherosclerosis and conveys a significant health burden globally. Critical limb ischaemia encompasses the most severe consequence of PAD. Our previous studies indicate that microRNA let-7g prevents atherosclerosis and improves endothelial functions. This study aimed to investigate whether and how let-7g therapy may improve blood flow to ischaemic limbs. The present study shows that let-7g has multiple pro-angiogenic effects on mouse ischaemic limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…PAD affects ~20% of the population aged >55 years, worldwide (3). The Inter-Society Consensus for the Management of Peripheral Arterial Disease (TASC II) determined that the prevalence of asymptomatic PAD is ~3–10% and is increasing to 15–20% in people aged >70 years worldwide (4). Critical limb ischemia (CLI) is the most severe clinical manifestation of PAD and may cause intermittent claudication, gangrene and foot ulcers (5).…”
Section: Introductionmentioning
confidence: 99%
“…PAD affects ~20% of the population aged >55 years, worldwide (3). The Inter-Society Consensus for the Management of Peripheral Arterial Disease (TASC II) determined that the prevalence of asymptomatic PAD is ~3–10% and is increasing to 15–20% in people aged >70 years worldwide (4). Critical limb ischemia (CLI) is the most severe clinical manifestation of PAD and may cause intermittent claudication, gangrene and foot ulcers (5).…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that let-7g can reduce atherosclerotic change by improving endothelial functions and by reducing oxLDL uptake by VSMC and endothelial cells [ 12 , 13 , 26 ]. Here we demonstrated an additional role of let-7g in macrophages, which further supports the importance of let-7g in maintaining vascular health.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by our group reported that let-7g directly targets and suppresses LOX-1 ( 25 ). Further studies by our group have reported that let-7g improves several endothelial functions by causing a decrease of senescence, inflammation and monocyte adhesion, and an increase of angiogenesis ( 12 , 25 , 26 ). The present study aimed to investigate whether let-7g also provides endothelial protection via a LOX-1-independent mechanism.…”
Section: Introductionmentioning
confidence: 87%